Effectiveness of Epidermal Growth Factor Receptor (EGFR) Tyrosine Kinase Inhibitor (TKI) on Life Expectancy in Non-Small Cell Lung Cancer Patients in Medan City - Harahap, Putri Wulandari; Tarigan, Setia Putra; Soeroso, Noni Novisari; Ashar, Taufik (Journal of Society Medicine, 2025)
Introduction: Non-small cell lung cancer (NSCLC) is strongly linked to epidermal growth factor receptor (EGFR) mutations, with tyrosine kinase inhibitors (TKIs) serving as a primary treatment. While TKIs demonstrate substantial antitumor effects, resistance differs across generations. This study evaluates the impact of first- and second-generation EGFR TKIs on the survival outcomes of NSCLC patients in Medan. Method: A retrospective cross-sectional study was conducted on 67 EGFR-positive NSCLC patients treated with TKIs between 2017 and 2022. Medical records from four hospitals-Haji Adam Malik Hospital, Elisabeth Hospital, Prof. Dr. Chairuddin Panusunan Lubis USU Hospital, and Pirngadi Hospital-were analyzed. Patients aged >18 years with EGFR mutations (exon 18, 19, or 21) and complete records were included. Survival outcomes, including Progression-Free Survival (PFS), Median Survival Time (MST), and Overall Survival (OS), were compared using the Mann-Whitney test. Results: All 67 patients received either first- or second-generation TKIs. Statistical analysis revealed that patients treated with second-generation TKIs had significantly better PFS, MST, and OS than those receiving first-generation TKIs (p < 0.05). Conclusion: This retrospective study faced limitations due to incomplete data and did not assess adverse effects. However, findings indicate that second-generation EGFR TKIs provide superior survival benefits for NSCLC patients compared to first-generation TKIs. Further prospective studies are needed to validate these results and explore the impact of treatment-related toxicity.